Islam and HIV/AIDS compassion and humanity: Confidentiality and testing issues and challenges - Ismail, Rokiah (1998)
The HIV epidemic started in the Western Hemisphere in the late 1970s. The first case of AIDS was detected amongst gay men in California in 1981 with the detection of a rare lung infection called Pneumocystis carinii Pneumonia (PCP). This was later linked to sexual activities and multiple partner change among these man.